Efficacy and safety of bisphosphonates on childhood osteoporosis secondary to chronic illness or its treatment: a meta-analysis - Huawei Zhao; Yunfei Ding; Jufei Yang; Yijun Luo; Zhenghao Xu; Jing Miao (SAGE Publishing, 2022)
Background: Bisphosphonates are a type of medication that prevents the loss of bone density. Secondary childhood osteoporosis reduces bone strength and results in an increased risk of fragility fracture. This meta-analysis aims to explore the efficacy and safety of bisphosphonates on secondary childhood osteoporosis. Methods: We performed a systematic search of PubMed, Cochrane library, and Web of Science databases up to 31 July 2022 to screen for random clinical trials (RCTs) on bisphosphonate treatment for childhood secondary osteoporosis. Data from selected studies, mainly changes in lumbar spine (LS) bone mineral density (BMD), changes in LS BMD Z -scores, fracture events, and adverse events (AEs), were extracted and analyzed. Results: Nine RCTs ( n  = 429 in total) were included in our meta-analysis. The meta-analysis indicated that bisphosphonates improved the changes in LS BMD [mean difference (MD) = 0.04, 95% confidence intervals (CIs) = 0.01-0.07, p  < 0.01] and LS BMD Z -scores [MD = 0.52, 95% CI = 0.23-0.81, p  < 0.01]. Use of bisphosphonates did not increase the risk of AEs [odds ratio (OR) = 1.61, 95% CI = 0.87-2.99, p  = 0.13]. Subgroup analysis showed that routes of administration, but not causes of secondary osteoporosis, might influence the efficacy of bisphosphonates. IV bisphosphonates close to significantly improved the incidence of fracture (OR = 0.34, 95% CI: 0.11-1.08, p  = 0.07). Conclusions: The use of bisphosphonates improves LS BMD without increasing AE rates, which supports the clinical use of bisphosphonates in secondary childhood osteoporosis. Further large RCTs are still warranted, especially for their long-term effects on fracture rates.